Three GLI2 mutations combined potentially underlie non‐syndromic cleft lip with or without cleft palate in a Chinese pedigree. Issue 9 (6th August 2019) - Meng, Peiqi; Zhao, Huaxiang; Huang, Wenbin; Zhang, Yunfan; Zhong, Wenjie; Zhang, Mengqi; Jia, Peizeng; Zhou, Zhibo; Maimaitili, Gulibaha; Chen, Feng; Zhang, Jieni; Lin, Jiuxiang
Abstract: Background: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is the most common craniofacial birth defect. Its etiology is complex and it has a lifelong influence on affected individuals. Despite many studies, the pathogenic gene alleles are not completely clear. Here, we recruited a Chinese NSCL/P family and explored the candidate causative variants in this pedigree. Methods: We performed whole‐exome sequencing on two patients and two unaffected subjects of this family. Variants were screened based on bioinformatics analysis to identify the potential etiological alleles. Species conservation analysis, mutation function prediction, and homology protein modeling were also performed to preliminarily evaluate the influence of the mutations. Results: We identified three rare mutations that are located on a single chromatid (c.2684C > T_p.Ala895Val, c.4350G > T_p.Gln1450His, and c.4622C > A_p.Ser1541Tyr) in GLI2 as candidate causative variants. All of these three mutations were predicted to be deleterious, and they affect amino acids that are conserved in many species. The mutation c.2684C > T was predicted to affect the structure of the GLI2 protein. Conclusion: Our results further demonstrate that GLI2 variants play a role in the pathogenesis of NSCL/P, and the three rare missense mutations combined are probably the potential disease‐causing variants in this family. Abstract : We recruited a Chinese NSCL/P family and identified three rare missense mutations that are located on a single chromatid in GLI2 as candidate causative variants in this pedigree. Our results further demonstrate that GLI2 variants play a role in the pathogenesis of NSCL/P